PENGARUH FORMULASI TEPUNG BATANG, DAUN DAN BUNGA KECOMBRANG (Nicolaia speciosa Horan) TERHADAP KARAKTERISTIK DAN DAYA SIMPAN CUKO PEMPEK - Fitriansyah, Idil; Muchsiri, Mukhtarudin; Alhanannasir, Alhanannasir (Universitas Muhammadiyah Palembang, 2017)
This research method is an experiment using a randomized block design (RAK) nonfactorial. Factors treatment which starch formulation stems, leaves and flowers kecombrang (F) and which consists of four (4) formulation of treatment and repeated 4 (four) times. Each treatment is F1 (Formulation Flour Trunk 1%: Leaves 2%: Interest 3%), F2 (Formulation Flour Trunk 2%: Leaves 3%: Interest 1%) F3 (Formulation Flour Trunk 3%: Leaves 1%: flowers 2%) F4 (Formulation Flour Trunk 2%: leaves 2%: 2% interest). The parameters observed in this study, for chemical analysis includes total acid and pH levels prior to storage on day 0 and after storage at day 12, while the organoleptic tests include color, flavor and aroma in cuko pempek prior to storage on day 0 and after storage at day 12 as well as physical observations done visually by looking at the signs of froth and viscosity changes during storage cuko pempek with intervals of 3 days until day 12. The results showed that the powder formulations influence stems, leaves and flowers kecombrang the characteristics and storability cuko pempek very significant effect on total acid before storage at day 0 and after storage on the 12th day, a very significant effect on the pH cuko pempek before storage at day 0 and after storage at day 12. The results of organoleptic test showed that the powder formulations influence stems, leaves and flowers kecombrang significantly affect aroma before storage at day 0 and after storage on the 12th day. No real effect on the taste cuko pempek prior to storage on day 0 and significantly affect flavor cuko pempek after storage on the 12th day and no real effect on the color cuko pempek before storage at day 0 and after storage at day 12. The test results storability by visual observation of the presence or absence of foaming and viscosity changes in cuko pempek during storage of 12 days all treatments showed no foam and no change of viscosity on cuko pempek generated during storage day 0 to day 12.